EFFICACY AND SAFETY OF SUGAMMADEX VERSUS NEOSTIGMINE FOR REVERSAL OF NEUROMUSCULAR BLOCKADE IN TOTAL LAPAROSCOPIC HYSTERECTOMY: EXPERIENCE FROM A RESOURCE-LIMITED SETTING. - Dr Mutthineni.sushma; Dr Vaishali kotambkar; Dr Virendra modi (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Background: In many government and teaching hospitals, quantitative neuromuscular monitoring is unavailable, and reversal of neuromuscular blockade (NMB) relies on clinical signs and qualitative peripheral nerve stimulation when possible. Sugammadex offers rapid, predictable reversal of aminosteroid NMB and greater hemodynamic stability while neostigmine remains the conventional agent despite slower onset and suspected residual blockade during recovery. This study compared the clinical efficacy and safety of sugammadex versus neostigmine in total laparoscopic hysterectomy (TLH) patients in a resource-limited setting.Methods: This observational case series included 50 ASA I–II female patients undergoing TLH under general anesthesia with vecuronium-induced NMB between January 2024 and June 2025 at a tertiary care government hospital. Due to unavailability of quantitative train-of-four monitoring, reversal was initiated at the standardized clinical endpoint of adequate spontaneous ventilation and purposeful movement, with peripheral nerve stimulator assessment when available. Patients received either sugammadex 2 mg/kg IV (n = 25) or neostigmine 50 μg/kg IV with glycopyrrolate 10 μg/kg IV (n = 25). Primary outcome was time from reversal to extubation. Secondary outcomes included hemodynamic stability, postoperative nausea/vomiting (PONV), clinically suspected residual blockade, and PACU readiness.Results: Sugammadex achieved faster extubation than neostigmine. Hemodynamic stability was greater in the sugammadex group, with fewer episodes of bradycardia and hypotension. PONV and clinically suspected residual blockade were more frequent in the neostigmine group. No major complications occurred in either group.Conclusion: Even without quantitative monitoring, sugammadex provided faster, more predictable recovery and greater hemodynamic stability compared with neostigmine in total laparoscopic hysterectomy patients. Its judicious use in resource-limited hospitals may enhance safety and efficiency, though cost remains a barrier.